Past Experiences of Getting Bullied and Assaulted and Posttraumatic Stress Disorder (PTSD) after a Severe Traumatic Event in Adulthood: A Study of World Trade Center (WTC) Responders. Issue 2 (7th February 2020) - Mukherjee, Soumyadeep; Clouston, Sean; Bromet, Evelyn; Leibowitz, George S.; Scott, Stacey B.; Bernard, Kristin; Kotov, Roman; Luft, Benjamin
ABSTRACT: Although experiencing bullying and other forms of assault is associated with adverse physical, emotional, and psychological consequences, the long-term consequences, especially in the aftermath of a severe trauma in adulthood, is not known. This study examined the relationship between history of being bullied and/or assaulted and posttraumatic stress disorder (PTSD) symptoms among responders to the World Trade Center (WTC) disaster. During 2015–2016, a modified life events checklist was administered to responders at Stony Brook WTC Health Program. WTC-related PTSD symptoms were assessed by PTSD checklist (PCL). Longitudinal mixed models examined associations between bullying, other forms of assault, and severity and chronicity of PTSD symptoms. Approximately, 13% of 920 responders had probable WTC-PTSD (PCL≥44). Being bullied in childhood was associated with increased odds of WTC-PTSD (adjusted odds ratio [aOR] = 7.34; 95% confidence interval [CI] = 2.12–25.34), adjusted for demographics, other stressors, and WTC exposures. PTSD odds decreased over time among those not bullied (aOR 0.82; 95% CI: 0.73–0.92), but not among victims. Experiencing physical, sexual, or verbal assaults during adulthood also had a significant association with WTC-PTSD (aOR 4.64; 95% CI: 1.98–10.92). Findings suggest being bullied in childhood and/or assaulted in adulthood can increase PTSD risk and progression after mass trauma.